1995
DOI: 10.1007/bf02188772
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic factors in chronic subdural haematoma and causes of recurrence after drainage

Abstract: The radiological aspect, pathology, treatment and results of 132 subdural haematomas observed in 100 patients, are discussed. The majority of these cases were characterized by a nonhomogenous CT scan picture, resulting from repeated bleeding in a previous subdural haematoma evolving to chronicity, or in a pre-existent subdural hygroma. Taking aspirin may have constituted a predisposing factor in 16% of our patients, whilst coagulation disturbances, including anticoagulant treatment, were observed in another 6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 40 publications
3
55
2
4
Order By: Relevance
“…The causes, clinical characteristics, and therapeutic management of CSDH are well established; however, the detailed physiology, including the mechanisms of appearance with motor dysfunction in patients, is still controversial. [1][2][3][4] Diffusion tensor imaging (DTI) reveals the tissue microstructure and architecture of white matter tracts, including pyramidal tracts, and extracts the principal diffusivities, mean diffusivities (MD), and fractional anisotropy (FA). Previously, it was reported that decreased FA in the pyramidal tracts on DTI was associated with secondary degeneration and could be a reliable measure of motor weakness.…”
mentioning
confidence: 99%
“…The causes, clinical characteristics, and therapeutic management of CSDH are well established; however, the detailed physiology, including the mechanisms of appearance with motor dysfunction in patients, is still controversial. [1][2][3][4] Diffusion tensor imaging (DTI) reveals the tissue microstructure and architecture of white matter tracts, including pyramidal tracts, and extracts the principal diffusivities, mean diffusivities (MD), and fractional anisotropy (FA). Previously, it was reported that decreased FA in the pyramidal tracts on DTI was associated with secondary degeneration and could be a reliable measure of motor weakness.…”
mentioning
confidence: 99%
“…Geçirilmiş travma öyküsü, antikoagülan kullanımı ve alkolizm ile subdural hematom oluşma riski artmaktadır. Subdural hematomu olan 100 hastanın incelendiği bir çalışmada hastaların %80'inde travma öyküsü, %22'sinde pıhtılaşmayı bozan ilaç kullanımı ve %11'inde alkolizm tespit edilmiştir (5). Subdural hematom yaşlılarda ve erkeklerde daha fazla görülmektedir.…”
Section: Discussionunclassified
“…Arteriyel kaynaklı kanama sonucu da oluşabilmektedir (2,3). Yaşlılarda, alkoliklerde, beyin atrofisi olanlarda, intrakranial anevrizması olanlarda, antikoagülan ilaç kullananlarda ve travma geçirenlerde subdural hematom daha sık görülmektedir (4)(5)(6)(7). Subdural hematom travmadan itibaren hematomun ortaya çıkma süresine göre akut, subakut ve kronik olarak sınıflandırılmaktadır (8).…”
Section: Introductionunclassified
“…Geçirilmiş travma öyküsü, antikoagülan kullanımı ve alkolizm ile subdural hematom oluşma riski artmaktadır. Subdural hematomu olan 100 hastanın incelendiği bir çalışmada hastaların %80'inde travma öyküsü, %22'sinde pıhtılaşmayı bozan ilaç kullanımı ve %11'inde alkolizm tespit edilmiştir (5 Maxeiner (1), ölüm sebepleri kafa travması olan 45 kişilik kadavra çalışmasında vakaların 2/3'ünde kontüzyonun eşlik ettiği kanama sebebiyle subdural hematom oluştuğunu; 1/3'ünde ise kontüzyon olmaksızın beynin yüzeyel damarlarının rüptürü sonucu subdural hematom oluştuğunu tespit etmiştir. Bu çalışmada bazı vakaların arteriyel orijinli olduğu tespit edilse de çoğunlukla köprü venlerinde rüptür olduğu gözlenmiştir.…”
Section: Discussionunclassified